Pharmacokinetics of Anti-Epileptic Drugs and their Clinical Significance - Svein I. Johannessen (Behavioural Neurology)
The serum concentration achieved and maintained following the administration of a fixed drug dosage is a direct consequence of the interactions of a wide variety of interrelated processes, including drug absorption, distribution, metabolism, and excretion, and the physiological status of the patient. These interrelationships are reviewed with specific reference to the major anti-epileptic drugs, phenobarbitone, phenytoin, sodium valproate, and carbamazepine, as well as a new first-line antiepileptic, oxcarbazepine. Both older drugs, such as phenobarbitone and phenytoin, and newer drugs, such as carbamazepine (CBZ) and sodium valproate, have been studied extensively over the past years giving valuable information for drug treatment. An important feature of oxcarbazepine (OXC) , which was developed through minimal changes in the structure of CBZ in order to improve on the tolerability of CBZ without sacrificing efficacy, is that its metabolites do not include the 11-epoxide which has been implicated in the side-effects of CBZ. In man, OXC is metabolized to a monohydroxy derivative which has independent anti-epileptic properties. OXC seems to lack several disadavantageous pharmacokinetic properties common to other major anti-epileptic drugs. OXC does not influence its own metabolism after repeated administration, in contrast to the auto-induction displayed by CBZ. The metabolism of OXC is not influenced by anti-epileptic co-medication and does not influence the kinetics of other anti-epileptic drugs – or if it does, then to a lesser extent than CBZ.